SCHOOL BASED MANAGEMENT - Eneng Muslihah (Al Qalam, 2009)
School based management is the main issues in the educational quality improvement of both elementary and secondary education institutions in the world in the last three decades. It is the alternative school management believed to be potentially able to elevate the education quality. In Indonesia, it was introduced as early as the end of 1999 following the enactment of the decentralization policy. School based management, which is seen as a panacea of Indonesian education problems especially from primary up to senior secondary schools, when the 2003 Education Law No 20 was introduced, Indonesia formally adopted a policy of "school-based management" for the quality improvement of its 227.298 public and private schools, and madrasahs (Islamic schools), 47.813.166 students and 3.218.7 54 teachers. SBM in Indonesia is focused on the four aspects of basic education: quality, equality, relevance and efficiency. While international research has not yet proved conclusively that schoolbased management improves student outcomes, but in Indonesia, the experience has been to a certain degree more positive.